Challenges and Coping Strategies of Maritime Instructors and Students in An Online Distance Learning (ODL) Environment - Mundo, David Gerald S. Del; Malangen, Ardrian D.; Cruz, Orlando Dela (Future Science / FSH-PH Publications, 2022)
ABSTRACT The COVID-19 pandemic has forced Higher Education Institutions (HEIs), Teachers and students to move into Online Distance Learning in the Philippines to continue providing quality education. The study centers on two factors the Challenges and Coping Strategies of Maritime Instructors and Students in an Online Distance Learning (ODL) Environment of Dr. Carlos S. Lanting College. A total of 157 respondents were involved in the study and distribution of questionnaires was done thru online. The descriptive and quantitative method of research is used in this study. As a result both the students and teachers used smartphones and laptop in Online Distance Learning but majority of the students have postpaid subscription service (42.38%) with an unstable and slow internet connectivity. Furthermore, the Challenges of Maritime Instructors and Students in an Online Distance Learning (ODL) Environment, the respondents generally answered “rarely” to the given statements as to academic requirements(M=2.08 and M=2.33), Learning Management System (M=1.96 and M=2.30), delivery of instructions (M=2.17 and 2.39) while data from learning environment (M=2.78 and M=2.73) is interpreted as